The Meaning of Blessings in Sharia-Based Online Business: A Study of Digital MSMEs - Busadi; Desy Bariyyatul Qibtiyah (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Economic developmentDigital technology encourages Micro, Small, and Medium Enterprises (MSMEs) to utilize digital technology in business activities, including Sharia-based businesses. This study aims to understand the meaning of blessings in Sharia-based online businesses at the Kopi Kecapi (Hani Green) MSME in Alastengah Village, Sumbermalang District, Situbondo Regency. This study also analyzes the implementation of business digitalization through the Shopee, TikTok Shop, and Tokopedia platforms, as well as the implementation of Sharia values ​​in digital business practices. The research method used is a qualitative approach with data collection techniques such as in-depth interviews, observation, and documentation. Data analysis is carried out through data reduction, data presentation, and thematic conclusion drawing. The results show that digitalization has a positive impact on business development, especially in expanding market reach and increasing sales turnover. The Shopee platform is the most dominant marketing medium because it is considered more effective, easy to use, and has a wider consumer reach than others. Digitalization also helps business actors market Arabica coffee products to various regions in Indonesia without requiring large promotional costs. Furthermore, the implementation of Sharia values ​​such as honesty, trustworthiness, fair pricing, and maintaining halal product certification are crucial factors in building consumer trust in digital transactions. In this study, blessings are not only interpreted as material benefits, but also encompass peace of mind, business sustainability, and benefits for the surrounding community, particularly local coffee farmers. This research demonstrates that digitalization and Sharia values ​​can work in harmony to support the success and blessings of Sharia-based digital MSMEs.